Psychological Impact of Speech Delay On Family Dynamics: A Qualitative Study of Parents' Experiences And Coping Mechanisms - Widiastuti, Endang; Rosdiana Zulfany, Naila; Sugiarti, Rini; Suhariadi, Fendy (CV. Inara, 2025)
Speech delay in children is a communication development disorder that can significantly affect family dynamics. This study aims to explore the psychological experiences of parents of children with speech delay, as well as the coping mechanisms they apply. Using a qualitative literature review and phenomenological perspective, this study analyzes various scientific sources to understand the psychological impact of speech delay on parents and families. The results show that parents often experience higher levels of stress, anxiety, and depression compared to parents of normally developing children. Social stigma and cultural pressure also contribute to feelings of isolation and helplessness. Effective coping mechanisms, such as social support and involvement in therapy, can help parents overcome these challenges. This study recommends the development of comprehensive and interdisciplinary psychological support programs, as well as increased public awareness to reduce stigma. In addition, it is important to create strong social support networks for families, including support groups and digital platforms. By understanding parents' experiences and the factors that influence their coping mechanisms, this study is expected to contribute to the development of better interventions and support the psychological well-being of families facing speech delays.